Hubungan Usia dan Paritas Ibu Hamil dengan Kejadian Preeklampsia di RSKD Ibu dan Anak Siti Fatimah Makassar: The Relationship between Age and Parity of Pregnant Women and the Incidence of Preeclampsia in the Siti Fatimah Makassar Mother and Child Hospital - Nasution, Evita Sarah; Miswani Mukani Syuaib; Alifia Ayu Delima (Prodi Kebidanan Universitas Islam Negeri Alauddin Makassar, 2024)
Introduction Based on data from the World Health Organization (WHO) in 2021, 810 women die every day due to complications during pregnancy and childbirth. Preeclampsia is a complication of pregnancy, where preeclampsia is a type of hypertension in pregnancy with a gestational age above 20 weeks accompanied by impaired organ function that was previously normotensive. The purpose of this study was to determine the relationship between age and parity of pregnant women with the incidence of preeclampsia and the relationship between preeclampsia and birth weight at the Siti Fatimah Women and Children Hospital in Makassar. Method This research method is a quantitative research with an observational approach and using a cross sectional method. Samples were taken by total sampling method. The number of samples was 91 obtained from medical records. Data were processed and analyzed using the Chi square test p<0.05 in the SPSS program. Result The results showed that there was a significant relationship between the age of pregnant women and the incidence of preeclampsia (p=0.041), there was a significant relationship between parity of pregnant women and the incidence of preeclampsia (p=0.016), and there was a significant relationship between preeclampsia and the incidence of LBW (p = 0.023). Conclusion The conclusion of this study is that there is a relationship between the age and parity of pregnant women with the incidence of preeclampsia and there is a relationship between preeclampsia and birth weight